Instrumente de politici publice în sistemul de furnizare a serviciilor sociale - Petrescu, Claudia; Rusu, Octavian (Calitatea Vieții, 2008)
How can we make an efficient public policy in social services delivery in Romania? The purpose of this article is to make a diagnosis of public policy instruments in social services delivery in Romania: public – private partnership and social contracting. The principles of government reform emphasis the importance of efficiency in public expenditure, improving steering and customer services. Public – private partnership and social contracting are public policy instruments that can be used to accomplish the principles of public administration reform. Starting with the presentation of social services financing forms in European Union and with the cooperation models between NGOs and government, we make an analysis of Romanian public policy in social services delivery.